“Heading for Extinction”: the representation of scientific knowledge in Extinction Rebellion's recruitment talks - Thierry, Aaron (Frontiers in Communication, 2023)
This study examines how the climate action group Extinction Rebellion represents scientific knowledge in the public presentations used to recruit new members. Using a combination of semi-structured interviews and recordings of the talks and comparing them across four versions, we examine how the talk developed and identify four distinct modes of science communication. This analysis also highlights that many factors shape the mode of science communication employed, with the outcome particularly influenced by the editors' concept of how to best motivate action, as well as changes in the wider communication environment and the evolution of the movement's strategic aims. We note the way in which the modes are expressions of “boundary work” seeking to either include or exclude scientific views the group perceives as either aligning with, or running counter to, their political goals.